Digital Technologies and the Reformatting of Values in the Post-Truth Era - Zhakin, S.M.; Mukan, N. (Karagandy University of the name of acad. E.A. Buketov, 2025)
This article critically examines how digital technologies are reshaping public values in the post-truth era. Bringing together insights from philosophy, sociology, media studies, and cognitive science, it considers how algorithmic personalization, emotional engagement, and surveillance capitalism are redefining traditional concepts of truth, power, privacy, and autonomy. The study identifies six key transformations: the rise of synthetic media destabilizing evidence-based knowledge, influence-based epistemologies replacing institutional gatekeepers, and conflicts between algorithmic efficiency and substantive justice. The findings illustrate a shift from truth as factual accuracy to truth as emotional engagement, and from autonomy as individual freedom to autonomy mediated by algorithmic systems. The final recommendations include regulatory harmonization, the development of an ethical platform, data trust models, cooperative ownership structures, and lifelong digital literacy training. Ultimately, the article offers a normative framework and practical ways to align digital innovation with democratic and ethical values.
Keywords: data colonialism; values; democratic deliberation; digital humanism; influencer epistemology; algorithmic personalization; post-truth; digital technologies